Circadian periodicity of cerebral blood flow revealed by laser-Doppler flowmetry in awake rats: relation to blood pressure and activity - Wauschkuhn, Constantin Aurel; Witte, Klaus; Gorbey, Stefan; Lemmer, Björn; Schilling, Lothar (American journal of physiology. Heart and circulatory physiology, 2005)
Cardiovascular parameters such as arterial blood pressure (ABP) and heart rate display pronounced circadian variation. The present study was performed to detect whether there is a circadian periodicity in the regulation of cerebral perfusion. Normotensive Sprague-Dawley rats (SDR, ∼15 wk old) and hypertensive (mREN2)27 transgenic rats (TGR, ∼12 wk old) were instrumented in the abdominal aorta with a blood pressure sensor coupled to a telemetry system for continuous recording of ABP, heart rate, and locomotor activity. After 5-12 days, a laser-Doppler flow (LDF) probe was attached to the skull by means of a guiding device to measure changes in brain cortical blood flow (CBF). After the animals recovered from anesthesia, measurements were taken for 3-4 days. The time series were analyzed with respect to the midline estimating statistic of rhythm (i.e., mean value of a periodic event after fit to a cosine function), amplitude, and acrophase (i.e., phase angle that corresponds to the peak of a given period) of the 24-h period. The LDF signal displayed a significant circadian rhythm, with the peak occurring at around midnight in SDR and TGR, despite inverse periodicity of ABP in TGR. This finding suggests independence of LDF periodicity from ABP regulation. Furthermore, the acrophase of the LDF was consistently found before the acrophase of the activity. From the present data, it is concluded that there is a circadian periodicity in the regulation of cerebral perfusion that is independent of circadian changes in ABP and probably is also independent of locomotor activity. The presence of a circadian periodicity in CBF may have implications for the occurrence of diurnal alterations in cerebrovascular events in humans.